Maurice Blanchot e a literatura: uma experiência outra - Almeida, Marcela Moura (2012)
This study of Maurice Blanchot s thought, specifically the books The Space of Literature, The Infinite Conversation, and The Book to Come, identifies the notions that the author develops regarding Literature and Art, such as Unworking, the Outside, and the Neutral. In order to follow Blanchot s more general theorization on the statutes of Art, it was at first necessary to contrast it with the tradition which mainly comes from Romanticism, but also from Heidegger. From a different perspective, this study explores what Blanchot considers to be the singularity of the space of literature, its impersonal dimension, which is understood to be the indelible mark that his work left among such thinkers as Foucault and Deleuze, thus affecting, beginning with Literary Theory, the field of Contemporary Philosophy